Polymorphisms Associated With Metabolic Dysfunction-Associated Steatotic Liver Disease Influence the Progression of End-Stage Liver Disease - Zehra N. Kocas-Kilicarslan; Zeliha Cetin; Lanuza A.P. Faccioli; Takashi Motomura; Sriram Amirneni; Ricardo Diaz-Aragon; Rodrigo M. Florentino; Yiyue Sun; Iris Pla-Palacin; Mengying Xia; Mark T. Miedel; Takeshi Kurihara; et al. (Gastro Hep Advances, 2024)
Background and Aims: Chronic liver injury that results in cirrhosis and end-stage liver disease (ESLD) causes more than 1 million deaths annually worldwide. Although the impact of genetic factors on the severity of metabolic dysfunction-associated steatotic liver disease (MASLD) and alcohol-related liver disease (ALD) has been previously studied, their contribution to the development of ESLD remains largely unexplored. Methods: We genotyped 6 MASLD-associated polymorphisms in healthy (n = 123), metabolic dysfunction-associated steatohepatitis (MASH) (n = 145), MASLD-associated ESLD (n = 72), and ALD-associated ESLD (n = 57) cohorts and performed multinomial logistic regression to determine the combined contribution of genetic, demographic, and clinical factors to the progression of ESLD. Results: Distinct sets of factors are associated with the progression to ESLD. The PNPLA3 rs738409:G and TM6SF2 rs58542926:T alleles, body mass index (BMI), age, and female sex were positively associated with progression from a healthy state to MASH. The PNPLA3 rs738409:G allele, age, male sex, and having type 2 diabetes mellitus were positively associated, while BMI was negatively associated with progression from MASH to MASLD-associated ESLD. The PNPLA3 rs738409:G and GCKR rs780094:T alleles, age, and male sex were positively associated, while BMI was negatively associated with progression from a healthy state to ALD-associated ESLD. The findings indicate that the PNPLA3 rs738409:G allele increases susceptibility to ESLD regardless of etiology, the TM6SF2 rs58542926:T allele increases susceptibility to MASH, and the GCKR rs780094:T allele increases susceptibility to ALD-associated ESLD. Conclusion: The PNPLA3, TM6SF2, and GCKR minor alleles influence the progression of MASLD-associated or ALD-associated ESLD. Genotyping for these variants in MASLD and ALD patients can enhance risk assessment, prompting early interventions to prevent ESLD.